The echo of things : the lives of photographs in the Solomon Islands - Wright, Christopher (Christopher J.) (Objects/histories., 2013)
The Echo of Things is a compelling ethnographic study of what photography means to the people of Roviana Lagoon in the western Solomon Islands and a provocative inquiry into our own understandings of photography.